POLEMIK ALIRAN ISLAM KLASIK TENTANG IMAN, KUFUR, AKAL DAN WAHYU - Ahmadi Husain (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2015)
This article discusses the polemic streams in the classical Islamic concept of faith, kufr, reason and revelation. The authors conclude that flow Khawarij said that people who receive tahkim are infidels, while the most extreme flow said anyone who did not emigrate into place, then he infidels and must be killed. While Flow Murji'ah said that people who receive tahkim not a pagan, but a believer, because he justified God in his heart and diiqrarkan with oral. Another with the flow Mu'tazilah, they say people who commit major sins is not a believer nor infidel, but fasiq. Flow Asha'ira said that anyone who sins is a big believer fasiq, and punishment in the hereafter, it is up to the will of God. Flow Maturidiyyah say that the great sin, not eternal hell. While the problem of reason and revelation, the authors came to the conclusion that the flow Mu'tazila give a great sense role rather than revelation. While Flow Asha'ira provide reasonable role that small and more emphasis on revelation. Maturidiyyah flow Samarkand say that knowing Allah, the obligation to know God, and knowing good and bad, all of which can be known by reason. While revelation can only know the obligation to do good and bad. Maturidiyyah flow Bukhara argued that reason and revelation gets the same portion. Intellect can know God and knows to do good and bad. While revelation can know the obligation to know God and the obligation to do good and bad.